The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.neuron.2012.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Inactivation Modifies Monkey Visuomotor Behavior

Abstract: SUMMARY A critical technique for understanding how neuronal activity contributes to behavior is determining whether perturbing it changes behavior. The advent of optogenetic techniques allows the immediately reversible alteration of neuronal activity in contrast to chemical approaches lasting minutes to hours. Modification of behavior using optogenetics has had substantial success in rodents, but has not been as successful in monkeys. Here we show how optogenetic inactivation of superior colliculus neurons in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 15 publications
3
127
0
2
Order By: Relevance
“…The maximum total light power density applied in this study was 100 mW/mm 2 , similar to what was used in the first electrophysiological demonstrations of optogenetics in the primate (19,61), as well as to what has been used for optogenetic modulation of superficial cortical neurons through a window on the brain (62,63). However, it is much lower than subsequent primate studies that reported behavioral changes using maximal light power densities ranging from several hundred milliwatts per square millimeter to >10 W/mm 2 (11)(12)(13)(14)(15)49).…”
Section: Significancementioning
confidence: 57%
See 2 more Smart Citations
“…The maximum total light power density applied in this study was 100 mW/mm 2 , similar to what was used in the first electrophysiological demonstrations of optogenetics in the primate (19,61), as well as to what has been used for optogenetic modulation of superficial cortical neurons through a window on the brain (62,63). However, it is much lower than subsequent primate studies that reported behavioral changes using maximal light power densities ranging from several hundred milliwatts per square millimeter to >10 W/mm 2 (11)(12)(13)(14)(15)49).…”
Section: Significancementioning
confidence: 57%
“…A pioneering primate optogenetics study (15) in the superior colliculus noted changes in saccade metrics (latency, velocity, and end points) without behavioral performance changes, implying that these metrics are altered at lower levels of inactivation than are needed to disrupt behavior. Previously, we have not had the means to inactivate with the temporal specificity seen using optogenetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optogenetics have been used in experimental organisms from C. elegans, zebrafish to mice, primates to analyze neural circuits relevant for many behaviors, from motor behavior (Cavanaugh, Monosov et al 2012) to learning and memory (Liu, Ramirez et al 2012). With the proof of principle demonstration that optogenetics can be safely performed in non-human primates (Han, Qian et al 2009), optogenetics has been explored for its translational potential in treating blindness (Doroudchi, Greenberg et al 2011).…”
Section: Application Of Optogeneticsmentioning
confidence: 99%
“…Le fait de concentrer ainsi la lumière expose au danger d'induire un échauffement local du parenchyme cérébral à proximité de l'extrémité de la fibre optique [10]. Ainsi, pour la SYNTHÈSE REVUES par des études comportementales [21,30]. Le bénéfice thérapeutique de protocoles utilisant la neuromodulation optogénétique n'a en revanche été évalué que dans un petit nombre de modèles de maladies neurologiques chez le rongeur.…”
Section: Des Obstacles à Surmonter Pour Une Utilisation De La Neuromounclassified